Cost-effectiveness analysis of statins in primary care: results from the Arteris cohort study (Swiss Medical Weekly, 2021)
BACKGROUND The Swiss Federal Office of Public Health performed a health technology assessment regarding statins in primary care. The chosen models may lead to a situation where a clinically indicated statin therapy is estimated not to be cost effective. METHODS We performed a cohort study regarding cardiovascular events, comparing SCORE and AGLA risk categories with tertiles of carotid plaque burden and used two models for cost-effectiveness analysis of high-potency statins. RESULTS Subjects (n = 2842) were followed up for 5.9 ± 2.9 years with the occurrence of 154 cardiovascular events (extrapolated 10-year risk was 9.2%). Carotid plaque imaging (total plaque area, TPA) significantly improved cardiovascular risk prediction compared with AGLA and SCORE for event-free survival prediction, test accuracy (discrimination) and calibration. Discrimination was significantly improved by about 4% with the inclusion of TPA. Cost-effectiveness analysis using quality-adjusted life years (QALYs) and sensitivity analyses (based on 16 models) ranged between CHF 144,496 and −128,328 per QALY. Cost-effectiveness analysis using direct and indirect costs showed that a treat-them-all strategy in the Swiss population would be cost effective with a return-on-investment per patient in 10 years of between CHF 4442 and 19,059, and the use of carotid imaging was also cost effective (incremental cost-efficiency ratio −2.97 to −7.86). CONCLUSIONS Carotid ultrasound significantly improved cardiovascular risk stratification and is cost effective. The Swiss Medical Board QALY model presents several drawbacks, which are shown in our sensitivity analysis, where results vary considerably and are not useful for clinical decision making. A “treat them all” strategy with statins in the Swiss population aged 30–65 years may be cost effective, when indirect costs of avoidable cardiovascular events are included, even at an unacceptably low value of a statistical life year.